Advancing nitrocellulose thermal stability through the incorporation of ion-exchanged ZSM-5 zeolite for enhanced performance - Memdouh Chebbah; Ahmed Fouzi Tarchoun; Fouad Benaliouche; Amir Abdelaziz; Djalal Trache (FirePhysChem, 2025)
In this study, cellulose nitrate (NC), a highly energetic polymer, was supplemented with two distinct classes of stabilizing agents: the usual diphenylamine (DPA) and zeolite molecular sieves (ZSM-5) that were ion-exchanged with transition metal ions, namely copper, silver, and cobalt. The primary objective was to assess the efficacy of these Cu, Ag, and Co-ion-exchanged ZSM-5 microporous materials as stabilizers for NC in comparison to the pristine NC and sample stabilized with DPA. To study their molecular compatibility and chemical compositions, the prepared samples underwent structural characterization employing advanced analytical methods. FTIR and XRD results revealed that the morphology and the original physical and chemical properties of NC matrix were preserved. Additionally, the accelerated thermal aging analysis of the prepared samples demonstrated an enhancement in the thermal stability and overall characteristics. The thermal behavior of the different samples was also investigated by TGA, revealing that the incorporation of 3 wt.% of the Cu, Ag, and Co -ion-exchanged ZSM-5 zeolites as stabilizers considerably affected the thermolysis of NC. Specifically, the weight loss of samples was notably reduced, indicating a remarkable decrease in the thermal decomposition of NC when doped with the zeolite molecular adsorbents. In contrast, the DPA stabilizer exhibited inferior performance in mitigating the pyrolysis of NC. Furthermore, the influence of diverse stabilizers on the thermal decomposition kinetics of NC was studied based on advanced model-free kinetic approaches, namely TAS and VYA/CE. Kinetic results unveiled that the incorporation of Cu, Ag, and Co ion-exchanged ZSM-5 adsorbents provides a pronounced enhancement in the thermal stability of NC. Notably, these zeolite-based stabilizers led to an increase in the activation energy barrier, thereby contributing to improved thermal stability.